2020
DOI: 10.1108/tr-11-2019-0459
|View full text |Cite
|
Sign up to set email alerts
|

Gaze and tourist-host relationship – state of the art

Abstract: Purpose The purpose of this paper is to offer an up-to-date review of the gaze, proposing new research agendas with regard to the various gazes actively operating at destinations. Design/methodology/approach The study thoroughly and systematically reviewed the existing literature by gathering papers related to gaze research in tourism contexts. Analysis of existing knowledge is centered around the gaze and a triadic framework among three key stakeholders. Findings A theoretical schema of the gaze was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…The keywords of “Chinese tourist visual experience” and “Chinese tourist perception (of destination/nature/landscape/culture/people/food and so forth)” was developed accordingly to prevent any missed data. The researchers have excluded those samples in the selection process which either probe a “reverse gaze” or “liminal gaze” – that is, Chinese hosts’ gaze upon the guests (Lin and Fu, 2020) – or use the term “gaze” casually and interchangeable with something else (e.g. gift-purchasing) (Moufakkir, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The keywords of “Chinese tourist visual experience” and “Chinese tourist perception (of destination/nature/landscape/culture/people/food and so forth)” was developed accordingly to prevent any missed data. The researchers have excluded those samples in the selection process which either probe a “reverse gaze” or “liminal gaze” – that is, Chinese hosts’ gaze upon the guests (Lin and Fu, 2020) – or use the term “gaze” casually and interchangeable with something else (e.g. gift-purchasing) (Moufakkir, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Debates have also assessed whether the tourist gaze can be thought of as positive, negative or mixed that shoulders on both subjects and the object of the gaze (Chan, 2006;Edensor, 2001;Maoz, 2006;Moufakkir, 2011). Lin and Fu (2020) systematically analyzed 34 literature papers directly associated with gaze with the focus of gaze and tourist-host relationship. The analysis has identified both the subjective and objective nature of the gaze and they recommend more comprehensive and systematic investigations of the gaze.…”
Section: Introduction and Methodologymentioning
confidence: 99%
“…Out of multi-faced gazes, the gaze literature is dominated by host-guest encounters. In their study, Lin and Fu (2020) introduced a theoretical framework that elaborated on the gaze notion along with the host-guest relationship. Accordingly, three fractions of gaze research have been identified: the gaze of the tourists, the gaze of the hosts and gaze constructed during tourist-host interactions.…”
Section: Fragmented Conceptions In Gazementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that race, class, and gender have significantly impacts on travel perceptions and experiences (Brown and Osman, 2017). Different cultural convention shape tourists’ gazes (Lin and Fu, 2020; Leri and Theodoridis, 2020; Rojek and Urry, 2002; Stylidis, 2020), which are also influenced by their geographical backgrounds. As the factors influencing tourist perceptions are diverse and elusive, these theorizations about tourists’ gazes require further exploration and elucidation.…”
Section: Literature Reviewmentioning
confidence: 99%